2015
DOI: 10.1152/japplphysiol.01050.2014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caffeine and maltodextrin mouth rinsing on P300, brain imaging, and cognitive performance

Abstract: Caffeine (CAF) and maltodextrin (MALT) mouth rinses (MR) improve exercise performance. The current experiment aims to determine the effect of CAF and MALT MR on cognitive performance and brain activity. Ten healthy male subjects (age 27 ± 3 yr) completed three experimental trials. Each trial included four Stroop tasks: two familiarization tasks, and one task before and one task after an MR period. The reaction time (in milliseconds) and accuracy (percent) of simple, congruent, and incongruent stimuli were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
78
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 39 publications
5
78
0
4
Order By: Relevance
“…Effect sizes for GLM were calculated using partial eta square ( ɳ p 2 ). Secondly, to specifically test effects of nutritional supplements and RPE, we also reported probabilistic magnitude-based inferences about all the variables using methods described by Hopkins et al [43] which has been applied in several recent nutritional studies [21,44,45]. Data were log-transformed prior to analyses to reduce bias arising from non-uniformity of error.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Effect sizes for GLM were calculated using partial eta square ( ɳ p 2 ). Secondly, to specifically test effects of nutritional supplements and RPE, we also reported probabilistic magnitude-based inferences about all the variables using methods described by Hopkins et al [43] which has been applied in several recent nutritional studies [21,44,45]. Data were log-transformed prior to analyses to reduce bias arising from non-uniformity of error.…”
Section: Methodsmentioning
confidence: 99%
“…Supporting this idea, it has been observed that the sole presence of CHO in the mouth, prior to its ingestion, induced an increase in corticomotor pathway excitability [20]. Besides these effects in motor areas, an increase in brain activity of some areas (i.e., the dorsolateral prefrontal cortex, the orbitofrontal cortex and the striatum), known to be involved in attention and reward, has also been observed after MR [13,21]. Because of the key-role of these brain areas in executive functions, performance in cognitive tasks could also be influenced; this needs to be further investigated.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Caffeine (1,3,7 Trimethylxanthine) is one of the most widely used ergogenic aids by elite athletes to increase sports performance in the world. With its removal of the World Anti-Doping Agency's list of controlled substance in 2004, there have been so many research conducted related to caffeine's ergogenic potential on various performance parameters as aerobic endurance, sprinting performance, muscular strength (Glaister et al, 2012).…”
Section: Introductionmentioning
confidence: 99%